PENGARUH PENGETAHUAN, KETRAMPILAN, DAN KEMAMPUAN SUMBER DAYA MANUSIA TERHADAP KINERJA UMKM DI KECAMATAN KARE KABUPATEN MADIUN - Pitoyo, Didik Joko; Handayani, Wahyu Prabawati Putri; Kurniawati, Dyah (Universitas Of Surakarta, 2023)
Abstract The primary objective of this study is to assess the statistical significance of the impact of knowledge, skills, and abilities on the performance of Micro, Small, and Medium Enterprises (MSMEs). The research encompasses MSME actors within Kare District, Madiun Regency, forming the population. Employing a saturated sampling technique, the study selected a sample consisting of 50 respondents who met the established criteria.The analytical approach adopted for this research involves multiple linear regression analysis, providing a comprehensive examination of the relationships between variables. The results of the analysis indicate that knowledge significantly influences the performance of MSMEs. Similarly, the skill variable exhibits a noteworthy impact on MSME performance, and the ability variable also demonstrates a significant effect on MSME performance.The research findings suggest that practitioners in the MSME sector should prioritize continuous improvement in their knowledge, skills, and abilities. By enhancing these key factors, MSMEs can optimize their overall performance in the business landscape.